A cross-sectional study on depression among school going adolescent girls in Barabanki district, Uttar Pradesh, India - Shukla, Nirpal Kaur; Shukla, Mukesh; Ahmad, Siraj; Shukla, Ram; Khan, Zainab (International Journal of Contemporary Pediatrics, 2016)
Background: Depression is one of the common and ignorant psychiatric problems in adolescents now days. It has profound adverse effect on their physical as well as mental health. The objective of this study was to study the prevalence of depression among school going adolescent girls. Methods: A cross sectional study was conducted among 336 school going adolescent girls in Barabanki district from June 2016 to September 2016. Multistage sampling was used to enroll the study subjects. Bio-social parameters such as age, socioeconomic status etc. were assessed by direct interview of adolescent girl as well as its confirmation with school records. Six items KADS (Kutcher Adolescent Depression Scale) was used for assessment of depression among adolescent girl. Results: Out of 336 adolescent girls screened 18.7% were found positive for depression. Lower socio-economic status was found as one of the independent predictor of depression. Girls belonging to lower socioeconomic groups (odds ratio ([OR] 2.08; 95% confidence interval [CI] 1.18-3.21; p = 0.03) were more susceptible for depression. However on multiple logistic regression no statistical association was observed between depression with respect to age group, class, religion, caste and mothers education, and type of family (p>0.05). Conclusions: The study highlights need for timely diagnosis and treatment of problem through school based periodic screening programmes. There is also need of increasing awareness among teachers and parents about depression.